Comparison of Fast Food Restaurant at A and W with Sabana Fried Chicken - Pradini, Gagih; Agustiani, Fitri; Prabu Santoso, Bintang; Liora, Devina Nisa; Fitria, Putri Maulida; Ananda, Tiara Martha (Akademi Komunitas MAPINDO, 2023)
Restaurant is a business that has developed quite rapidly, because competition between companies is getting tighter because of the increasing number of similar restaurants offered. With this competition, it will have an impact on the company because the tighter the competition, consumers will hold a selection of the product. The food business has significant growth, because the increasing number of places to eat such as cafes, restaurants, restaurants continues to grow in number. This journal discusses the comparison of the two brands, including A and W Restaurant and Sabana Fried Chicken which both sell food of the same type but with differences in origin, where A and W is an external product and Sabana is a local product. Each has its own analysis which we discuss in this journalKeywords: Tourism, Food, Hospitality, Marketing Strategy, Food and Beverages Business